Spinocerebellar Ataxia 36: From Mutations Toward Therapies - Lopez, Samuel; He, Fang (Frontiers in Genetics, 2022)
Spinocerebellar ataxia 36, or SCA36, is a type of repeat expansion related neurodegenerative disorder identified a decade ago. Like other SCAs, the symptoms of SCA36 include the loss of coordination like gait ataxia and eye movement problems, but motor neuron-related symptoms like muscular atrophy are also present in those patients. The disease is caused by a GGCCTG hexanucleotide repeat expansion in gene Nop56, and the demographic incidence map showed that this disease was more common among ethnic groups of Japanese Spanish descendants. Although the exact mechanisms are still under investigation, the present evidences support that the expanded repeats may undergo repeat expansion-related non-AUG initiated translation and these dipeptide repeat products could be one of the important ways to lead to pathogenesis. Such studies may help develop potential treatments for this disease.